2021
DOI: 10.1080/23273798.2021.1946108
|View full text |Cite
|
Sign up to set email alerts
|

Eyetracking while reading passives: an event structure account of difficulty

Abstract: Among existing accounts of passivisation difficulty, some argue it depends on the predicate semantics (i.e. passives are more difficult with subject-experiencer than agent-patient verbs). Inconsistent with the accounts that predict passive difficulty, Paolazzi et al. (2019) found that passives were read faster than actives at the verb and object by-phrase in a series of self-paced reading experiments, with no modulation of verb type. However, self-paced reading provides limited direct measurement of late revis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Finally, our results suggest that NA children are more accurate in actives (99% and 97% for actional and nonactional verbs, respectively) than passives (88%) independent of the verb type and passive type. This accords with earlier observations (e.g., Maratsos et al, 1985;Meng & Bader, 2021;Paolazzi et al, 2021), which consistently reported passives to be more errorful than actives.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Finally, our results suggest that NA children are more accurate in actives (99% and 97% for actional and nonactional verbs, respectively) than passives (88%) independent of the verb type and passive type. This accords with earlier observations (e.g., Maratsos et al, 1985;Meng & Bader, 2021;Paolazzi et al, 2021), which consistently reported passives to be more errorful than actives.…”
Section: Discussionsupporting
confidence: 93%
“…Actional verb (3a) is higher in transitivity than nonactional verb (3b), because the latter does not have properties such as affectedness, intentionality, or change of state. The asymmetry between actional and nonactional passives has been widely replicated in English (Bidgood et al, 2020;Gorden & Chafetz, 1990;Hirsch & Wexler, 2006;Orfitelli, 2012;Paolazzi et al, 2021;Sudhalter & Braine, 1985) and in other languages investigating children's passive acquisition (e.g., Agostinho, 2020, for Portuguese;Gavarró & Parramon, 2017, for Catalan;Koutamanis, 2015, for Dutch;Oliva & Wexler, 2018, for Spanish;Perovic et al, 2012, for Serbian;Safari & Mehrpour, 2015, for Persian;Volpato et al, 2015, for Italian). Nguyen and Pearl's (2021) recent meta-analysis also evoke semantic factors to explain away the predicated-based asymmetry of actional and nonactional passives on passive acquisition.…”
Section: )mentioning
confidence: 96%
“…Thus, both active object experiencer verbs and active subject experiencer verbs led to greater difficulty, albeit at different points in the sentence, with only the greater difficulty for active object experiencer verbs consistent with the predictions of the thematic-grammatical alignment hypothesis. Nevertheless, other studies using a variety of measures including SPR, eye-tracking while reading, and MEG have generally found results consistent with the thematic-grammatical alignment hypothesis (Brennan & Pylkkänen 2010;Paolazzi 2018;Paolazzi et al 2019Paolazzi et al , 2021.…”
Section: Alignment In Comprehensionmentioning
confidence: 71%
“…For instance, studies on passive sentence comprehension consistently demonstrate difficulties in offline tasks across languages ( Ferreira, 2003 ; Sung et al, 2017 ; Paolazzi et al, 2019 ; Sung et al, 2020 ), whereas online measures often report no significant difficulties or even better performance. Traxler et al (2013) found that passive sentences were read faster than active ones in self-paced reading tasks, while Paolazzi et al (2021) observed greater latency in eye-tracking studies.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, studies on passive sentence comprehension consistently demonstrate difficulties in offline tasks across languages (Ferreira, 2003;Sung et al, 2017;Paolazzi et al, 2019;Sung et al, 2020), whereas online measures often report no significant difficulties or even better performance. Traxler et al (2013) found that passive sentences were read faster than active ones in self-paced reading tasks, while Paolazzi et al (2021) observed greater latency in eye-tracking studies. Similarly, such inconsistencies arise in studies on relative clauses, with object relatives are generally considered more challenging than subject relative clauses (Waters and Caplan, 2001;Waters and Caplan, 2005;Kemper and Liu, 2007;Caplan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%